Kesiagaan Dalam Perencanaan Anggaran Penanggulanan Bencana Banjir Kabupaten Bandung - Ririn Karlina (Department of Public Administration, 2021)
The main problem of this research is that there is no special budget for flood disaster management in Cibiru Hilir Village. This study aims to analyze the design of village funds in flood disaster management and analyze village efforts to raise additional funds for flood disaster management in Cibiru Hilir village. The research method used is descriptive qualitative. Collecting data using interviews, observation, and documentation study. Data analysis was carried out, namely data reduction, data presentation, and concluding. The results of this study indicate that the embodiment of the principle of transparency is quite well implemented with the ease of expressing opinions and openness, the accountability process for budget management issued, accountability to the public, and follow-up on irregularities by the rules, and the application of value for money in 2020 and 2021. Still not running optimally in the absence of a special budget for flood disaster management and 2018 and 2019 it has been running economically and flood disaster management services have been running well.